Distinguishing postpartum and antepartum depressive trajectories in a large population-based cohort: the impact of exposure to adversity and offspring gender. Issue 7 (11th September 2017) - Denckla, C. A.; Mancini, A. D.; Consedine, N. S.; Milanovic, S. M.; Basu, A.; Seedat, S.; Spies, G.; Henderson, D. C.; Bonanno, G. A.; Koenen, K. C.
Abstract: Background: Distinguishing temporal patterns of depressive symptoms during pregnancy and after childbirth has important clinical implications for diagnosis, treatment, and maternal and child outcomes. The primary aim of the present study was to distinguish patterns of chronically elevated levels of depressive symptoms v. trajectories that are either elevated during pregnancy but then remit after childbirth, v. patterns that increase after childbirth. Methods: The report uses latent growth mixture modeling in a large, population-based cohort ( N = 12 121) to investigate temporal patterns of depressive symptoms. We examined theoretically relevant sociodemographic factors, exposure to adversity, and offspring gender as predictors. Results: Four distinct trajectories emerged, including resilient (74.3%), improving (9.2%), emergent (4.0%), and chronic (11.5%). Lower maternal and paternal education distinguished chronic from resilient depressive trajectories, whereas higher maternal and partner education, and female offspring gender, distinguished the emergent trajectory from the chronic trajectory. Younger maternal age distinguished the improving group from the resilient group. Exposure to medical, interpersonal, financial, and housing adversity predicted membership in the chronic, emergent, and improving trajectories compared with the resilient trajectory. Finally, exposure to medical, interpersonal, and financial adversity was associated with the chronic v . improving group, and inversely related to the emergent class relative to the improving group. Conclusions: There are distinct temporal patterns of depressive symptoms during pregnancy, after childbirth, and beyond. Most women show stable low levels of depressive symptoms, while emergent and chronic depression patterns are separable with distinct correlates, most notably maternal age, education levels, adversity exposure, and child gender.